Optimal Biomethane Injection into Natural Gas Grid – Biogas from Palm Oil Mill Effluent (POME) in Malaysia. (May 2017) - Hoo, Poh Ying; Patrizio, Piera; Leduc, Sylvain; Hashim, Haslenda; Kraxner, Florian; Tan, Sie Ting; Ho, Wai Shin
Abstract: The Malaysian government aims to facilitate the renewable energy (RE) sector by introducing the National Renewable Energy Policy and Action Plan during 2010. 4, 000 MW of installed RE capacity is targeted by 2030, with 410 MW biogas capacity. Palm oil mill effluent (POME), agro-based industries and farming industries are identified as potential sources of biogas. It was studied that more than 500 kt of biomethane could be produced yearly if all the POME is treated anaerobically. The utilization of biomethane has remained unexplored for its injection into natural gas grid. This papers aims to identify the potential of POME biomethane injection into natural gas grid by using the BeWhere model, a techno-economic spatial explicit model. The locations, capacity and technology of biogas refinery plants will be identified based on cost minimization of the full supply chain of biogas production. The result shows that 135 - 227 biogas plants were selected, supplying 40% - 67% residential fossil gas demand, under different carbon price implementation and fossil gas subsidy scenarios.